Performance Evaluation of Distribution Node in Case of LEACH Implementation on Wireless Sensor Network - Bagas Mardiasyah Prakoso; Ahmad Zainudin; Prima Kristalina; Rizqi Fauzil Azhar (Jurnal Elektronika dan Telekomunikasi, 2018)
Wireless sensor networks consisting of sensor nodes can be used as an effective tool for collecting data in various situations. Nodes are usually placed randomly in an area to perform sensing and monitor various parameters related to environmental conditions in various locations. One of the major problems in wireless sensor networks is developing energy-efficient routing protocols that have a significant impact on the overall life of sensor networks so it is important to make energy savings in these limited energy sources to extend network life. This paper proposes a hardware design and Low-Energy Adaptive Clustering Hierarchy (LEACH) routing protocol configuration for power saving by utilizing cluster head selection mechanism. The cluster head selection process is performed periodically based on LEACH algorithm enables the node to have the best lifetime responsible for communication between the nodes and the server as well as the effort to save energy consumption of limited energy sources to extend network life. So that makes the process of sending information more effective and optimal. The system has been able to display data information along with the position of nodes in the web server with an average of 42 seconds of computing time in a rotation of the system so that it can be done 85 times in 1 hour. The system is able to provide real-time information with a throughput of more than 1.052 Kbps and packet loss of no more than 6.7%. In addition, energy savings can up to 6.5% of the existing energy in a lithium battery.